High-Affinity, Non-Peptide Agonists for the ORL1 (Orphanin FQ/Nociceptin) Receptor - Röver, Stephan; Adam, Geo; Cesura, Andrea M; Galley, Guido; Jenck, François; Monsma, Frederick J; Wichmann, Jürgen; Dautzenberg, Frank M (Journal of medicinal chemistry, 2000)
The discovery of 8-(5,8-dichloro-1,2,3,4-tetrahydro-naphthalen-2-yl)-1-phenyl-1,3,8-triazaspiro[4.5]decan-4-one, 1a, as a high-affinity ligand for the human ORL1 (orphanin FQ/nociceptin) receptor led to the synthesis of a series of optimized ligands. These compounds exhibit high affinity for the human ORL1 receptor, exhibit moderate to good selectivity versus opioid receptors, and behave as full agonists in biochemical assays. In this paper we present the synthesis, structure−activity relationship (SAR), and biochemical characterization of substituted 1-phenyl-1,3,8-triazaspiro[4.5]decan-4-ones culminating in the discovery of 8-(5-methyl-1,2,3,4-tetrahydro-naphthalen-1-yl)-1-phenyl-1,3,8-triazaspiro[4.5]decan-4-one, 1p, and 8-acenaphten-1-yl-1-phenyl-1,3,8-triazaspiro[4.5]decan-4-one 1q, two high-affinity, potent ORL1 receptor agonists with good to moderate selectivity versus the other opioid receptors.